2016
DOI: 10.1093/aje/kwv273
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Correction of Misclassification of Pertussis in Vaccine Effectiveness Studies: How Much Does Underreporting Matter?

Abstract: Diagnosis of pertussis remains a challenge, and consequently research on the risk of disease might be biased because of misclassification. We quantified this misclassification and corrected for it in a case-control study of children in Philadelphia, Pennsylvania, who were 3 months to 6 years of age and diagnosed with pertussis between 2011 and 2013. Vaccine effectiveness (VE; calculated as (1 - odds ratio) × 100) was used to describe the average reduction in reported pertussis incidence resulting from persons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…We provided the correction equations for VE estimates in case of non-differential single source (either exposure or disease) misclassification (Section 2.2). Other correction methods include amongst others probabilistic bias analyses [ 24 , 25 ], Bayesian bias analyses [ 26 – 28 ], modified maximum likelihood methods [ 29 ] and imputation-like methods [ 30 33 ]. All these methods require assumptions on or estimates of the disease- and exposure misclassification parameters, which—if deemed required—can be obtained using internal or external validation studies.…”
Section: Discussionmentioning
confidence: 99%
“…We provided the correction equations for VE estimates in case of non-differential single source (either exposure or disease) misclassification (Section 2.2). Other correction methods include amongst others probabilistic bias analyses [ 24 , 25 ], Bayesian bias analyses [ 26 – 28 ], modified maximum likelihood methods [ 29 ] and imputation-like methods [ 30 33 ]. All these methods require assumptions on or estimates of the disease- and exposure misclassification parameters, which—if deemed required—can be obtained using internal or external validation studies.…”
Section: Discussionmentioning
confidence: 99%
“…Suspected, probable, and confirmed pertussis cases were included. 19 Pertussis remains highly underreported, 20 , 21 and only cases of patients who were symptomatic and whose caregivers sought medical help through PHSKC were included. Information on age, sex, and home address for patients was available.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, quantitative bias analyses extend beyond the bounds of data accuracy: similar approaches can handle cases of selection bias and residual confounding (again, see Lash et al, 2009 , and Smith et al, 2021 ). Beyond the case study demonstrated in this article, we refer readers to these other examples of quantitative bias analysis applied to misclassified outcome data ( Bodnar et al, 2010 ; Burstyn et al, 2020 ; Goldstein et al, 2016 ; Goldstein et al, 2021 ; Jurek & Maldonado, 2016 ; Srugo et al, 2021 ; Wesselink et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%